Addressing abortion through individual and community-level determinants: Evidence from Southern Ethiopia - Amanuel Yoseph; Lakew Mussie; Mehretu Belayneh; Francisco Guillen-Grima (PLoS ONE, 2026)
Background Abortion remains a significant public health concern in Ethiopia, contributing to maternal morbidity and mortality. Understanding the individual- and community-level determinants of abortion is essential to inform targeted interventions. This study aimed to assess the prevalence and multilevel determinants of abortion among women of reproductive age in Hawela Lida District, Southern Ethiopia. Methods A community-based cross-sectional survey was conducted from February to March 2025 among 3,526 women of reproductive age who experienced a pregnancy within the 12 months preceding the survey. Data were collected using a structured, pretested questionnaire and analyzed with Stata v18. Multilevel mixed-effects logistic regression was employed to identify individual- and community-level determinants, adjusting for potential confounders. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were reported. Results The overall prevalence of abortion was 18.5% (95% CI: 15.8–24.8). At the individual level, women without formal education were more likely to experience abortion than those with formal education (AOR = 2.61; 95% CI: 1.36–4.54). Women with unplanned pregnancies (AOR = 2.72; 95% CI: 1.62–4.68) and those who were non-autonomous in decision-making (AOR = 2.21; 95% CI: 1.51–5.02) also had higher odds of abortion. At the community level, rural residence (AOR = 2.19; 95% CI: 1.65–4.23), greater distance to the nearest health facility (AOR = 2.34; 95% CI: 1.21–5.01), and low mass media exposure (AOR = 1.82; 95% CI: 1.23–4.12) were significantly associated with abortion. Conclusion Abortion in Hawela Lida District was associated with both individual and community factors, including women’s education, pregnancy planning, autonomy, place of residence, mass media exposure, and health facility accessibility. Integrated interventions that strengthen family planning, promote women’s empowerment, improve service accessibility, and provide accurate reproductive health information are urgently needed to reduce abortion prevalence and improve maternal health outcomes in Ethiopia.